The Effect of Workload and Work Stress on Quiet Quitting with Burnout as a Mediating Variable in Generation Z Employees - Erika Fataa Cahyaningrum; Teguh Hardi Raharjo (Universitas KH. Abdul Chalim Mojokerto, 2026)
The phenomenon of Quiet Quitting is one of the issues that is getting more and more attention in the world of work because it shows the tendency of employees to limit work involvement only to tasks and responsibilities that have been set without making additional contributions beyond formal obligations. This phenomenon is widely associated with Generation Z who have a high concern for work-life balance and mental health. The focus of this study is to analyze the role of burnout in the relationship between workload, work stress, and Quiet Quitting in Generation Z employees. The collected data is then processed using the PLS-SEM technique with the help of SmartPLS. The findings indicate that work stress contributes significantly to increased burnout and quiet quitting, while workload was not found to have a significant influence on both constructs. Burnout has also been shown to have a positive effect on quiet quitting. The results of the mediation test showed that burnout did not mediate the effect of workload on quiet quitting, but mediated the effect of work stress on quiet quitting through a complementary mediation mechanism. This finding confirms that work stress is a more dominant factor than workload in explaining the emergence of burnout and Quiet Quitting in Generation Z employees. Therefore, organizations need to prioritize work stress management and burnout prevention to minimize the tendency of Quiet Quitting in the work environment.